Aging, microglial cell priming, and the discordant central inflammatory response to signals from the peripheral immune system - Dilger, Ryan N.; Johnson, Rodney W. (Journal of leukocyte biology, 2008)
Recent studies suggest that activation of the peripheral immune system elicits a discordant central (i.e., in the brain) inflammatory response in aged but otherwise healthy subjects compared with younger cohorts. A fundamental difference in the reactive state of microglial cells in the aged brain has been suggested as the basis for this discordant inflammatory response. Thus, the aging process appears to serve as a “priming” stimulus for microglia, and upon secondary stimulation with a triggering stimulus (i.e., peripheral signals communicating infection), these primed microglia release excessive quantities of proinflammatory cytokines. Subsequently, this exaggerated cytokine release elicits exaggerated behavioral changes including anorexia, hypersomnia, lethargy, decreased social interaction, and deficits in cognitive and motor function (collectively known as the sickness behavior syndrome). Whereas this reorganization of host priorities is normally adaptive in young subjects, there is a propensity for this response to be maladaptive in aged subjects, resulting in greater severity and duration of the sickness behavior syndrome. Consequently, acute bouts of cognitive impairment in elderly subjects increase the likelihood of poor self‐care behaviors (i.e., anorexia, weight loss, noncompliance), which ultimately leads to higher rates of hospitalization and mortality.